2008
DOI: 10.1186/1749-799x-3-40
|View full text |Cite
|
Sign up to set email alerts
|

Sevoflurane requirement during elective ankle day surgery: the effects of etirocoxib premedication, a prospective randomised study

Abstract: Background: Anti-inflammatory drugs, NSAIDs, have become an important part of the pain management in day surgery. The aim of the present study was to evaluate the effect of Coxib premedication on the intra-operative anaesthetic requirements in patients undergoing elective ankle surgery in general anaesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…These characteristics make them attractive candidates for perioperative use (Viola et al 2007 ; Schwartz et al 2008 ). Etoricoxib (a new selective COX-2 inhibitor available in many countries) has been reported to reduce postoperative pain after orthopedic surgery (Toivonen et al 2007 ; Turan et al 2008 ). When administered postoperatively to patients who had undergone hip replacement, etoricoxib provided analgesia similar to controlled release naproxen and superior to placebo (Rasmussen et al 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…These characteristics make them attractive candidates for perioperative use (Viola et al 2007 ; Schwartz et al 2008 ). Etoricoxib (a new selective COX-2 inhibitor available in many countries) has been reported to reduce postoperative pain after orthopedic surgery (Toivonen et al 2007 ; Turan et al 2008 ). When administered postoperatively to patients who had undergone hip replacement, etoricoxib provided analgesia similar to controlled release naproxen and superior to placebo (Rasmussen et al 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, pre-emptive analgesia can reduce immediate postoperative pain and also prevent the development of chronic pain by decreasing the altered central sensory processing. 20,21 Several studies have examined of the use of etoricoxib and have confirmed its efficacy in providing pain relief after gynaecological procedures (Liu et al, 2005, 22 Chau-in et al, 2008 23 ), after laparoscopic surgery (Puura et al, 2006 6 ), after thyroid surgery (Smirnov et al, 2008 12 ), after orthopaedic surgery (Peter et al, 2012 24 , Rasmussen et al, 2005, 25 Ibrahim et al, 2008, 26 Sowbhagya et al, 2014 27 ) and after trauma surgery (Siddiqui et al, 2008). 28 Our work studies the efficacy of a single dose of etoricoxib administered preoperatively in reducing the intraoperative anaesthetic and postoperative analgesic requirements in patients undergoing open inguinal hernioplasty under general anaesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…Etoricoxib, a highly selective cyclooxygenase (COX)‐2 inhibitor available in many countries, has been reported to reduce postoperative pain after orthopaedic surgery (Turan, Hein, Jacobson, & Jakobsson, ). It's pharmacokinetics are linear at clinically relevant doses, and their half‐life (t1/2) of approximately 20 hr enables once‐a‐day dosing (Blaney Davidson et al, ).…”
Section: Introductionmentioning
confidence: 99%